Have large increases in fast track referrals improved bowel cancer outcomes in UK?. (10th November 2020) - Thompson, Michael; O'Leary, Daniel; Heath, Iona; Wood, Lynn Faulds; Ellis, Brian; Flashman, Karen; ,; Smart, Neil; Nicholls, John; Mortensen, Neil; Finan, Paul; Senapati, Asha; et al.
Abstract : More precise risk stratification is required to enable timely diagnosis of bowel cancer while avoiding unnecessary investigation, argue Michael Thompson and colleagues